Evaluation of community economic building movement policy in East Flores Regency - Dominikus Fernandez; Rikhardus Seran Klau; Adriana Rodina Fallo (goodwood publishing)
Purpose: The purpose of this study is to evaluate the Policy of Community Economic Building Movement in East Flores Regency. Research methodology: The research method used in this research is a descriptive research method with a qualitative approach. Results: The findings in this study are that there are many deficiencies in terms of both content of policy and policy implementation. Limitations: this research only discusses and evaluates the policies of community economic development movements in the East Flores district. Contribution: This research becomes scientific information for public administration science. Keywords: Evaluation, Empowerment